PENERAPAN ASAS FIRST TO FILE DALAM KASUS SENGKETA MEREK DAGANG: PERSEPEKTIF UNDANG-UNDANG MEREK DI INDONESIA - Julia Mahadewi, Kadek (LPSDI Bina Patria, 2025)
The increasingly rapid Industrial Trader has resulted in frequent trademark violations in the industrial world, trademarks are a form of Company product identity that needs to be protected by registering in accordance with the provisions of the MIG Law article 20. Trademark Rights Violations often occur in Indonesia, seeing article 21 paragraph 1 of the MIG Law containing the registration of the first to file principle, whoever registers first will receive protection. The case that can be seen here is the Aki GS brand against Aki Gisi, where the trademark registration was first obtained by Aki GS. The appearance of both is basically the same so that there is a trademark dispute problem, Aki Gs feels disadvantaged by Aki Gisi. This writing method uses a normative research method, the type of approach is the statutory approach and the case approach, there are two sources of legal materials, primary and secondary legal materials, Analysis of legal materials using qualitative descriptive. The results of this study Aki Gisi's trademark was canceled seeing the similarities in principle, the appearance of this battery is the same as a whole and is also a type of procurement of goods code 9 related to batteries. Dispute resolution is carried out through litigation through the Commercial Court to the Supreme Court.